2021
DOI: 10.1155/2021/4873678
|View full text |Cite
|
Sign up to set email alerts
|

Study of the G Protein Nucleolar 2 Value in Liver Hepatocellular Carcinoma Treatment and Prognosis

Abstract: LIHC (liver hepatocellular carcinoma) mostly occurs in patients with chronic liver disease. It is primarily induced by a vicious cycle of liver injury, inflammation, and regeneration that usually last for decades. The G protein nucleolar 2 (GNL2), as a protein-encoding gene, is also known as NGP1, Nog2, Nug2, Ngp-1, and HUMAUANTIG. Few reports are shown towards the specific biological function of GNL2. Meanwhile, it is still unclear whether it is related to the pathogenesis of carcinoma up to date. Here, our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…HCC frequently coexists with chronic liver conditions like cirrhosis, which can exacerbate the progression of HCC. This concomitance underscores the complex nature of HCC’s pathogenesis and highlights the importance of early intervention and comprehensive management of underlying liver conditions to mitigate the severity of HCC ( 17 , 18 ). Currently, the intricate mechanisms underpinning HCC are not fully understood.…”
Section: Discussionmentioning
confidence: 93%
“…HCC frequently coexists with chronic liver conditions like cirrhosis, which can exacerbate the progression of HCC. This concomitance underscores the complex nature of HCC’s pathogenesis and highlights the importance of early intervention and comprehensive management of underlying liver conditions to mitigate the severity of HCC ( 17 , 18 ). Currently, the intricate mechanisms underpinning HCC are not fully understood.…”
Section: Discussionmentioning
confidence: 93%
“…The GNL2 family encompasses two members, namely GNL3 (nucleoprotein) and GNL3-like (GNL3L) ( 36 ). While GNL3L functions as the vertebrate equivalent of the nucleostemin, GNL2 has a unique presence across both vertebrate and invertebrate species ( 37 ). The contribution of GNL2 to various cancers has been previously highlighted in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…As a protein-encoding gene, G protein nucleolar 2 (GNL2) goes by several other names, including NGP1 , Nog2 , Nug2 , Ngp-1 , and HUMAUANTIG . Dong et al ( 59 ) reported that HCC patients with high GNL2 expression had lower survival rates, and in vitro knockdown investigations demonstrated that decreasing GNL2 using siRNA inhibited HCC cell proliferation, migration, and invasion capabilities. Consequently, the model may be utilized to assess the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%